A revised dichotomous key to the snakes of Italy (Reptilia, Squamata, Serpentes), according to recent systematic updates - Di Nicola, Matteo Riccardo (Zootaxa, 2019)
The diffusion of “citizen science” brings considerable benefits to ecological research (Bonney et al. 2009; Dickinson et al. 2012) and involves an increasing use of data provided by “non-professionals” for the establishment of distribution atlases (for instance, through online platforms such as “iNaturalist”). Therefore, it is important that the presented data are sufficiently reliable and, for this reason, photographic documentation of what has been observed is always encouraged. In many cases, however, the circumstances or the conditions of the observed organism do not allow a photographic identification. Dichotomous keys are tools that, in addition to the use by technicians, researchers and students, can be useful to “non-professional” observers to improve the accuracy in the determination of observations to be submitted to the scientific community. This also applies to the herpetological field, and thus to this work, which offers an updated dichotomous key for the determination of Italian snakes (the first since the one published in Corti et al. (2011)) in light of the various systematic updates that affected this taxon.